Understanding Economic Growth Modern Theory and Experience - Sengupta, Jati (Springer New York, 2011)
Modern economies have undergone a dramatic change. There has been a shift from large scale material manufacturing to the design and application of new technology with R&D and human capital. The new information age has introduced significant productivity gains through increasing returns and learning by doing, which has challenged the traditional growth models based on competitive market structures. Institutions outside the traditional markets and the genetic principle of survival of the fittest have dominated the current theory of industry growth. This book coordinates and integrates the two strands of economic growth and development: the endogenous theory of growth and the extra-market models of evolutionary economics dominated by innovation efficiency. It presents this new paradigm in terms of both theory and historical experiences. The book addresses the role of innovations and human capital, the impact of information technology, the role of institutions as mechanisms of evolutionary economies and the experiences of Asian growth miracles, and will be of interest to readers in economics and political science concerned with economic growth and development.